Comparison of holotomographic microscopy and coherence-controlled holographic microscopy - Chvalova, Vera; Vomastek, Tomas; Grousl, Tomas (Journal of microscopy, 2024)
Quantitative phase imaging (QPI) is a powerful tool for label-free visualisation of living cells. Here, we compare two QPI microscopes - the Telight Q-Phase microscope and the Nanolive 3D Cell Explorer-fluo microscope. Both systems provide unbiased information about cell morphology, such as individual cell dry mass, perimeter and area. The Q-Phase microscope uses artefact-free, coherence-controlled holographic imaging technology to visualise cells in real time with minimal phototoxicity. The 3D Cell Explorer-fluo employs laser-based holotomography to reconstruct 3D images of living cells, visualising their internal structures and dynamics. Here, we analysed the strengths and limitations of both microscopes when examining two morphologically distinct cell lines - the cuboidal epithelial MDCK cells which form multicellular clusters and solitary growing Rat2 fibroblasts. We focus mainly on the ability of the devices to generate images suitable for single-cell segmentation by the built-in software, and we discuss the segmentation results and quantitative data generated from the segmented images. We show that both microscopes offer slightly different advantages, and the choice between them depends on the specific requirements and goals of the user.
Keywords: single-cell segmentation; quantitative phase imaging/microscopy; Cell Line; holografie; MDCK; Holography; buněčné linie; Microscopy; coherence-controlled holographic imaging/microscopy; Lasers; Rat2; kvantitativní fázové zobrazování; mikroskopie; lasery; holotomography; Quantitative Phase Imaging; dry mass content